Penguatan Karakter Siswa Sekolah Dasar Melalui Integrasi Kearifan Lokal dalam Proses Pembelajaran - Rida Jubaedah; Dini Anggraeni Dewi; Tuti Istianti (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
One of the strategic steps in strengthening character is integrating local wisdom into the learning process. Local wisdom reflects noble values such as mutual cooperation, tolerance, and environmental love, which have become guiding principles for the community. This approach is expected to shape a generation that excels not only in knowledge but also in strong character rooted in the nation's culture. Thus, education based on local wisdom can serve as a bridge to harmonize tradition with modernization in the era of globalization. This study uses the literature review method as an initial step in designing the research. The literature review involves searching and analyzing various sources, such as books, journal articles, and other publications relevant to the research topic. The results of this study prove that strengthening character education based on local wisdom, such as mutual cooperation, honesty, courtesy, and tolerance, is the main strategy to preserve cultural identity amid the waves of globalization. The integration of these values is carried out through the curriculum, experiential learning methods, and extracurricular activities relevant to students' lives.